دور الأحزاب السياسية في صنع السياسة العامة - ناصوري, أحمد; سمرة, ياسر (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تُعد الأحزاب السياسية من أهم التنظيمات السياسية التي تؤثر بشكل مباشر على سير وحركة النظام السياسي وضمان استمراره واستقراره، فهي تؤدي دوراً مهماً في تنشيط الحياة السياسية وصارت تُشكل ركناً أساسياً من أركان النظم الديمقراطية، فأداء الأحزاب ينعكس سلباً أو إيجاباً على نوعية الحياة السياسية وعلى مستوى التطور الديمقراطي والتحديث السياسي وفاعلية النظام السياسي الذي يُعدّ انعكاساً للنظام الحزبي السائد في الدولة. وللأحزاب السياسية دور مهم في صنع السياسة العامة وتأطيرها، حيث تُعد إحدى قنوات المشاركة السياسية للمواطن، وكذا إحدى قنوات الاتصال السياسي المنظّم في المجتمع، إذْ يعدّها علماء السياسة، الركيزة القوية والمنظمة للربط بين القمة والقاعدة وكمحطة اتصال لازمة بين المواطنين والسلطة.تحاول هذه الدراسة التعرّف على ماهية السياسة العامة التي هي في المقام الأول عملية سياسية تتميز بالصعوبة والتعقيد، وتختلف طبيعة وإجراءات وطرق صنعها من دولة إلى أخرى تبعاً للنظام السياسي ودور الأجهزة الحكومية وغير الحكومية، ومنها الأحزاب السياسية. كما تتناول دور الأحزاب السياسية في صنع السياسة العامة في الدولة، تخطيطاً وتنفيذاً وتقييماً، من خلال الوقوف على دورها في رسم وتخطيط السياسة العامة للدولة، لاسيما من خلال وجودها وتمثيلها في السلطة التشريعية. وكذلك الوقوف على دور الأحزاب في تنفيذ السياسة العامة من خلال مشاركتها في السلطة التنفيذية وحجم هذه المشاركة. وأيضاً معرفة دور الأحزاب في عملية تقييم السياسة العامة، لأن التقييم الفعَّال والموضوعي والحقيقي يُعدّ أساس نجاح السياسة العامة في تحقيق أهدافها. وخلصت الدراسة إلى أنَّ الأحزاب قد تكون مخططاً ومنفذاً ومقيماً للسياسة العامة إنْ وصلت إلى السلطة، وبالتالي ستقوم بتطبيق برامجها عن طريق القوانين التي ستسنها في (السلطة التشريعية) أو عن طريق تنفيذها للقوانين في (السلطة التنفيذية-الحكومة) أو عن طريق تواجدها في المعارضة، وهنا قد تقوم باستخدام وسائل وطرق عديدة للضغط والتأثير على السلطة. Political parties are of the most important political organizations which affect directly the movement of political system and guarantee its and stability and continuousness .They play an important role in activating political life . And they became an essential aspect of democratic systems . Performance of parties has it reflections positively or negatively on the quality of political life and on the level of democratic development and political modernization and activity of political system which is considered a reflection of the parties system that is dominant in the state . Political parties have an important role in making public policy and framing it as they are channels of political partnership of citizens, and organized political communication in society . Policy scientists consider them the strong organized basis for the connection of summit and base and a communication station which is necessary between citizens and authority .This study is an attempt to acknowledge public society which is a difficult and complex political process . The nature and procedures of its shaping differ from a state to another according to political system and the role of government and non-government entities and political parties are of them . The research deals with the role of political parties in shaping the public policy of the state , planning , execution and evaluation , by looking at their role in planning the public policy of the state mainly throughout their presence and representation in the legislative authority. And also by highlighting the role of parties in implementation of public policy throughout sharing in the executive authority and the volume of this partnership. And also knowing the role of parties in the process of evaluation of public policy, because actual, active and objective evaluation is the basis of the success of public policy in achieving its goals .The study finds out that parties can plan , implement and evaluate public policy, if they reach authority and in consequence they shall apply their programs via laws which they enact in (Legislative authority) or by implementation of laws in (Executive authority – Government)or by their presence in opposition and here they may use many methods and ways to exert pressure on and affect authority.